Institutional Framework for Protection of Geographical Indications in Tanzania: Examining the Challenges and Way Forward towards Effective Protection of Geographical Indications in the Country - Ndunguru , Adrian F.; Mwanga , Elia (International Journal of Business, Management and Economics, 2023)
The study is interested to review the challenges of the current Tanzania institutions framework dealing with protection of geographical indications with the view of exploring the alternative changes that can enable Tanzania to effectively deal with enforcement of domestic and international laws dealing with protection of geographical indications. In the end study recommends the possible wayward to strengthen the performance of the institutions dealing with protection and enforcement of geographical indications in Tanzania.